2015
DOI: 10.1111/geb.12328
|View full text |Cite
|
Sign up to set email alerts
|

Geographic patterns of diversification and the latitudinal gradient of richness of rocky intertidal gastropods: the ‘into the tropical museum’ hypothesis

Abstract: Aim To evaluate the existence of a latitudinal gradient of richness (LGR) in rocky intertidal gastropods and the role of evolutionary processes in shaping the LGR. Location The entire eastern Pacific coast, from Alaska to Tierra del Fuego, encompassing ca. 120° latitude. Methods The LGR was assessed using field surveys and a comprehensive literature dataset from 308 rocky intertidal sites, representing 328 species and 159 genera. The importance of geographic patterns of diversification in shaping the LGR was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…Along the coast of the eastern Pacific Ocean several studies have reported latitudinal patterns of species richness in northern or southern hemispheres (Roy, Jablonski, Valentine, & Rosenberg, ; Valdovinos, Navarrete, & Marquet, ; Rex, Crame, Stuart, & Clarke, ; Rivadeneira et al., ). So far, the few studies focused on inter‐hemispheric trends have documented similar patterns to those observed in terrestrial environments, with a marked poleward decrease in species richness (Hillebrand, ; Lyons & Willig, ; Rex et al., ; Roy et al., ; Willig & Lyons, ), and other studies have reported trends in species range sizes related to Rapoport's pattern (Mora & Robertson, ; Tomašových & Jablonski, ; Tomašových et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Along the coast of the eastern Pacific Ocean several studies have reported latitudinal patterns of species richness in northern or southern hemispheres (Roy, Jablonski, Valentine, & Rosenberg, ; Valdovinos, Navarrete, & Marquet, ; Rex, Crame, Stuart, & Clarke, ; Rivadeneira et al., ). So far, the few studies focused on inter‐hemispheric trends have documented similar patterns to those observed in terrestrial environments, with a marked poleward decrease in species richness (Hillebrand, ; Lyons & Willig, ; Rex et al., ; Roy et al., ; Willig & Lyons, ), and other studies have reported trends in species range sizes related to Rapoport's pattern (Mora & Robertson, ; Tomašových & Jablonski, ; Tomašových et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of species on rocky shores around the world is largely driven by broad-scale climatic regimes, associated with latitude and modified by ocean currents and upwelling regimes (Hutchins, 1947;Helmuth et al, 2006b;Fenberg et al, 2015). There are warm-and cold-water adapted species, leading to different species pools able to live in different biogeographic areas.…”
Section: Factors Influencing Biodiversity In Intertidal Rocky Habitatsmentioning
confidence: 99%
“…There are warm-and cold-water adapted species, leading to different species pools able to live in different biogeographic areas. The species pool is ultimately determined by phylogeographic processes associated with the evolutionary origin of species and their subsequent spread in response to tectonic and climatic processes over long geological timescales, including opening and closing of ocean basins (Rivadeneira et al, 2015). Natural biogeographical processes have been altered, however, by humanmediated transport of species around the world.…”
Section: Factors Influencing Biodiversity In Intertidal Rocky Habitatsmentioning
confidence: 99%
See 2 more Smart Citations